Software is the message. Few notes on aspects of digital literature - Franta, Tomas (Bohemica Olomucensia, 2018)
This study is intended as an introductory study of interactive web-based Reading-book of digital literature, which will be online in the second half of 2019 on digilit.upol.cz. The study gives a comprehensive and condensed introduction into issues of digital literature. It deals with the creative and theoretical history of digital literature and proposes a commentated overview of basic attributes of digital literature itself. It focuses on how software and technology are essential for the works of digital literature and what kind of unique possibilities they open for formal and content qualities of pieces of digital literature. It discusses issues of materiality, variability, interactivity and archiving of digital literature.
Keywords: digital literature; history of digital literature; aspects of digital literature; electronic literature; software; digital media